Analysis of the sorption-enhanced chemical looping biomass gasification process: Performance assessment and optimization through design of experiment approach. (15th September 2020) - Detchusananard, Thanaphorn; Im-orb, Karittha; Maréchal, François; Arpornwichanop, Amornchai
Abstract: In this study, the performance of high-purity hydrogen production through the sorption-enhanced chemical looping gasification (SECLG) process, involving a gasifier, calciner, and air reactor, was investigated. In this process, the biomass feedstock was wood residue, and steam, calcium oxide (CaO), and nickel oxide (NiO) were used as a gasifying agent, CO2 sorbent, and oxygen carrier, respectively. First, the influences of key operational parameters (i.e., steam to carbon (S/C) molar ratio, gasifying temperature, and NiO to carbon (NiO/C) molar ratio) on product gas yields and net energy consumption of the process were studied. According to the first and second laws of thermodynamics, performance indicators of the SECLG process demonstrated that increases in energy and exergy efficiencies occurred with increases in S/C molar ratio and/or gasifying temperature. Then, mathematical models indicative of correlations between energy efficiency, exergy efficiency, and major operating parameters (e.g., S/C molar ratio and gasifying temperature) were developed through the design of experiment (DOE) method and used for process optimization. The optimal conditions offering maximum energy (70%) and exergy (56%) efficiencies were a S/C molar ratio of 4.5 and gasifying temperature of 700 °C, under which all reactors operated at thermal self-sufficient conditions. Highlights: Sorption-enhanced chemical looping gasification (SECLG) process was investigated. Energy and exergy analyses were used to evaluate process performance. S/C ratio and gasifying temperature were the major operating parameters. Design of experiment (DOE) method are used for process optimization. The energy and exergy efficiencies of the process were 70 and 56%.